EVALUASI KELONGSORAN TANAH PADA BANTARAN SUNGAI KONTO DI KECAMATAN PUJON DAN PENANGANANNYA - Suhudi Suhudi; Maradona Supriyanto (Universitas Tribhuwana Tunggadewi, 2016)
Retaining wall serves to hold the soil and prevent it from sliding danger. Either as a result of rain load, heavy soil itself, also a result of the load that works on it. Nowadays, construction of retaining wall is very often used in civil works construction of a retaining wall even if it turns out the land is long enough known in the world. Landslide that occurred along the River Konto at Abdul Manan Wijaya Street Pujon caused by the dimensions of the retaining wall is too small so unstable to the safety factor (SF), the value of the safety factor in the review is a safety factor to bearing capacity , shear forces and stability against roll style. The purpose of this research is to analyze the cause of the collapse of the retaining wall and re plan retaining wall that had collapsed. The unstable retaining wall caused by shear force that is 1.28 < 1.5 (unsafe). The replan of the retaining wall by gravity type retaining wall with the rear side of upright because of this type is suitable for a high retaining wall. Dimensional stability toward sliding wall: 1.67 > 1.5 (safe) and stable toward the bolsters: 3.9 > 1.5 (safe).